Delirium Diagnostic and Classification Challenges in Palliative Care: Subsyndromal Delirium, Comorbid Delirium-Dementia, and Psychomotor Subtypes - Leonard, Maeve M.; Agar, Meera; Spiller, Juliet A.; Davis, Brid; Mohamad, Mas M.; Meagher, David J.; Lawlor, Peter G. (Journal of pain and symptom management, 2014)
Delirium often presents difficult diagnostic and classification challenges in palliative care settings. To review three major areas that create diagnostic and classification challenges in relation to delirium in palliative care: subsyndromal delirium (SSD), delirium in the context of comorbid dementia, and classification of psychomotor subtypes, and to identify knowledge gaps and research priorities in relation to these three areas of focus. We combined multidisciplinary input from delirium researchers and knowledge users at an international delirium study planning meeting and relevant PubMed literature searches as the knowledge synthesis strategy in this review. We identified six (SSD), 33 (dementia), and 44 (psychomotor subtypes) articles of relevance in relation to the focus of our review. Recent literature data highlight the frequency and impact of SSD, the relevance of comorbid dementia, and the propensity for a hypoactive presentation of delirium in the palliative population. The differential diagnoses to consider are wide and include pain, fatigue, mood disturbance, psychoactive medication effects, and other causes for altered consciousness. Challenges in the diagnosis and classification of delirium in people with advanced disease are compounded by the generalized disturbance of central nervous system function that occurs in the seriously ill, often with comorbid illness, including dementia. Further research is needed to delineate the pathophysiological and clinical associations of these presentations and thus inform therapeutic strategies. The expanding aged population and growing focus on dementia care in palliative care highlight the need to conduct this research.